Reservoir quality of Cenozoic carbonate buildups and coral reef terraces - Wilson, Moyra (Indonesian Petroleum Association, 2008)
Almost half of SE Asia's considerable hydrocarbon reserves are contained in carbonates. The majority of these reservoirs are Miocene buildups up to tens of kilometres across. However, with the exception of a few fields, there is little detailed data on how local depositional and diagenetic conditions influence the considerable heterogeneities in reservoir quality often encountered. This study focuses on factors influencing the facies, diagenetic and reservoir variability of comparable Modern, Quaternary and Neogene reef associated deposits from the Tukang Besi Archipelago, Central Indonesia.The Archipelago includes large atolls, a number of smaller buildups and 4 main islands each with modern rimmed shelves or fringing reefs. On the islands, over ten late Neogene and Quaternary coral reef terraces have been uplifted to maximum heights of ~300 m. Analysis of the modern deposits allows initial reservoir potential to be assessed and related to local environmental conditions. The influence of diagenesis on final reservoir quality is evaluated for the depositional facies exposed in the uplifted terraces. The overall spatial distribution of effective porosity across the area is strongly dependent on local energy conditions, water depth, carbonate producers, size of atolls or islands, climate and local meteoric diagenetic processes. This evaluation of spatial variability in carbonate reservoir characteristics provides much needed analogue data as the hydrocarbon industry focuses on improving recovery from existing fields and exploring for new reserves.